2018
DOI: 10.1029/2018rs006539
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Estimation of Agricultural Raised Bed Microwave Disinfection

Abstract: The use of electromagnetic fields to solve issues related to agriculture is an interesting, costeffective, and eco-friendly possibility to be explored. One of the most promising applications is the disinfection of soils obtained by microwave-induced heating. This work deals with the nonlinear computational modeling of such microwave heating of soils in metal raised bed cultivations within a greenhouse. By modeling the dielectric properties of soil, in terms of composition, moisture content, and actual temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The temperature distribution of deeper sites (for example, 5–10 cm in this study) depends on heat conduction and during conduction heat lost to the atmosphere causes cooler and hotter spots (i.e., inconsistency in soil heating) in the lower penetration depth, as detected in the microcosm of the present study (Figure S4). Relevant to this, Casu et al (2018) presented a one‐dimensional transmission‐line model to predict the feasibility of MW soil treatment for disinfestation purposes in raised‐bed agricultural systems. Their simulation represented the time required to attain the lethal temperature and its retention in the soil against various penetration depths to eradicate pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature distribution of deeper sites (for example, 5–10 cm in this study) depends on heat conduction and during conduction heat lost to the atmosphere causes cooler and hotter spots (i.e., inconsistency in soil heating) in the lower penetration depth, as detected in the microcosm of the present study (Figure S4). Relevant to this, Casu et al (2018) presented a one‐dimensional transmission‐line model to predict the feasibility of MW soil treatment for disinfestation purposes in raised‐bed agricultural systems. Their simulation represented the time required to attain the lethal temperature and its retention in the soil against various penetration depths to eradicate pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the feasibility of microwave disinfection, Casu et al [97] analyzed the microwave heating of the soils of bed cultivations within a greenhouse; the results showed that microwave disinfection was applicable to different planting patterns, and was also effective for soil-borne pests. Sun et al [98] experimented on the effect of the output power of the microwave, the treatment duration, and the soil humidity on the soil temperature.…”
Section: Physical Soil Disinfectionmentioning
confidence: 99%
“…At radio and microwave frequencies, ionic conduction and dipole rotation are the dominant loss mechanisms [39]. In addition to the material ionic conductivity and dipole rotation ability, permittivity depends on the material composition [28] and texture [40], and to a lesser extent on pressure [41]; however, the parameters that mainly affect this variable are frequency and temperature [41]. The frequency influence, in the case of pure liquids, is described by the Debye model [42], where the relaxation time of the material is also taken into account.…”
Section: Elements Of Dielectric Theorymentioning
confidence: 99%